Introduction - Ethridge, Alicia; Johnson, Paul (Groupwork, 2012)
This paper examines the theoretical underpinning of service learning, groupwork and other relevant pedagogies which together enhance and greatly enrich the learning opportunities for students. Following this the authors describe the development and growth of service learning at the University of Southern Maine. It is the authors’ belief that this modality enriches the academic experiences of students and faculty, and benefits not only the university community but also the wider community. The authors provide a number of accounts of how service learning has been infused into the curriculum. Finally, a number of personal narratives are provided which further exemplify the benefits of this approach to one’s education and foster a sense of social and civic responsibility. These tenets also coincide with the principles of groupwork and social work.